Hubungan antara Dukungan Sosial dan Problem-Focused Coping dengan Psychological Well-Being Siswa SMK Negeri 1 Wadaslintang - Riani, Amellia; Lutfi, Ika Kurniati; Prasetiyanti, Herlin (Universitas Pendidikan Indonesia Kampus Serang, 2022)
This research is motivated by the importance of social support, problem-focused coping, and psychological well-being for learners. Therefore, this study aimed to determine the relationship between social support and problem-focused coping with psychological well-being in students of the State Vocational School of 1 Wadaslintang. The approach used in this study is a quantitative approach to the type of correlation research. The population in this study were students of the State Vocational School of 1 Wadaslintang, totaling 1,148 students. The sample in this study was 300 students, the sample was taken using a simple random sampling technique. The data in this study were obtained using the social support scale, the problem-focused coping scale, and the psychological well-being scale. Test the validity of the instrument using expert judgment and test the reliability of the instrument is calculated using the Cronbach alpha coefficient. Data analysis in this study used regression analysis. The results of the research analysis showed an F value of 645.548 with a significance level of p = 0.000 (p 0.05). These results indicate that there is a positive relationship between social support and problem-focused coping with psychological well-being in students of the State Vocational School of 1 Wadaslintang. It means that if students have high social support and problem-focused coping, then students will also have high psychological well-being. The effective contribution of social support and problem-focused coping to psychological well-being is 81.30%, while 18.70% comes from other factors, meaning that those two factors contributed to more than half of students’ psychological well-being.